Traffic Congestion in Bangladesh- Causes and Solutions: A study of Chittagong Metropolitan City - Shamsher, Robaka; Abdullah, Mohamamd Nayeem (Asian Business Review, 2013)
One of the most challenging and complicated issues in city management in the present decade for Bangladesh is the traffic problem. It is a very common phenomenon in almost all the cities of Bangladesh. Presently, traffic congestion problem in Bangladesh are increasing at an alarming rate. The traffic problem has become to a very dangerous arena and has already implicit agonizing extent in the cities of Bangladesh. This type of study has been conducted in Dhaka but not in Chittagong city. Traffic management in Chittagong is not well organized as Dhaka so that the problem is becoming more complicated as the number of people in Chittagong is increasing and it is getting the priority after Dhaka. This article is dedicated to determine the current condition of traffic management in Chittagong City. This article explore the causes involved in traffic congestion  including heavy concentration of vehicles, absence of adequate public transport, inadequate road infrastructure, faulty signaling equipment and   poor  enforcement of traffic rules. At the end of the paper the researchers tried to identify the solution of traffic jam in Chittagong Metropolitan City.JELclassfication: M10, M14
Keywords: Traffic congestion; vehicles; traffic rules; Chittagong Metropolitan City